Research and evaluation in counseling - Erford, Bradley T. (Stamford, CT : Cengage Learning, 2015)
Research is often an intimidating topic in a counselor training program but it does not have to be. This text helps to alleviate readers' concerns while helping them learn what they need to know. It presents the most essential components of research and illustrates them with meaningful examples, enabling users to master each component. Recognizing that the profession of counseling has entered the age of accountability, this text helps to educate counselors and future counselors about research and evaluation procedures so that their treatment of clients can be more effective and efficient. Organized into three topical sections, this edition addresses the curricular requirements of the Council for Accreditation of Counseling and Related Educational Programs (CACREP), providing the latest information on research, statistics, and evaluation procedures.
Previous edition : 2008.
Includes bibliographical references and indexes.
Keywords: Counseling; Counseling psychology -- Research; Psychotherapy -- Research